Effect of temperature and sunshine on the productivity of rice crop - SASTRI, A. S. R. A. S.; RAI, S. K.; SRIVASTAVA , A. K.; CHAUDHARY, J. L. (MAUSAM, 1996)
Based on the experimental work with 8 different thermal and light environments, the effect of temperature and sunshine on rice crop (var : IR-36) was studied. It was found that the rice crop grown during winter/summer season experience, extremes of minimum temperature at seedling and vegetative stages and extemes of maximum temperature at reproductive and maturity stages. Correlation coeffcients between the grain yield and maximum and minimum temperature growing degree days and total number of sunshine hours at each of the growth stages.viz:. seedling. vegetative. reproductive and maturity stages were worked out. Multiple regression equation was worked out with 5 parameters upto vegetative stage to predict the grain yield of rice